Trouble Ticketing System Based Standard ISO10002: 2004 To Improve Handling of Complaints Responsibility - Ahmad Cucus; Marzuki Marzuki; Agus Sukoco; Maria Shusanti Febrianti; Huda Budi Pamungkas (Bandar Lampung University (UBL), 2012)
Trouble Ticketing System (TTS) is a mechanism that madean organization as a form of awareness of the partner organization, the TTS is a real form of Customer Relationship Management or CRM. TTS is the development of a complaints handling system that had been shaped by the conventional paper media, electronic switch in the form of an Internet-based media website.ISO10002:2004deals withthe complaintshandlingsystem, has two main objectives, namely tohandlecomplaintsproperlyso thatit givessatisfactionboth internallyand externally, the complaintis handledcanmakeaperformance improvementservices.With theimplementation of theISO10002: 2004onTTSwillincrease the level ofresponsibilityinthe handling ofcomplaints, becausetheISO10002: 2004allmechanismsanddevices inhandlingcomplaintsproperly managed.